Relevance of Character with Transformation of Values and Learning Styles in General Education - Ginting, Seriwati; Hartanti, Monica; Tjandra, Miki (Journal of Nonformal Education, 2021)
Character is believed to be a force that can sustain a person in all situations. This research was conducted when the pandemic was still hitting and during a new adaptation period. The pandemic causes the need for changes and adjustments in attending lectures. In the faculty of arts and design, most of the learning process is carried out through the assistance of student work. Lecturers and students meet face to face on campus. The pandemic is changing values and learning styles that require effort, willingness, and adaptability. This research examines the relevance of student character with the ability to follow the transformation of values, learning styles, and learning methods. The method used in this research is through interviews with students of the faculty of art and design, interviews with lecturers, limited surveys, and distributing questionnaires as an effort to collect information. All information will be sorted according to the aims and objectives of the research through data reduction.